Developmet the Complex Technology for Highly Concentrated Acid Solutions of Electroplating Industry - IVANENKO Olena; DOVHOLAP Sergii; NOSACHOVA Yuliia; PLASHYKHIN Sergii; PAVLIUK Nonna; SKLADANNYY Denys (Architecture, Civil Engineering, Environment)
The paper presents the results of research on the application of ion-exchange processes for the extraction of iron (II) and copper (II) ions from liquid acid wastes of electroplating production. In the course of experimental studies, it was shown that with an increase in the concentration of sulfuric acid, the total exchangeable dynamic capacity (TEDC) of the cationite significantly decreases both during the sorption of iron ions and during the sorption of copper ions. At the same time, an increase in the iron (II) ions concentration leads to a significant increase in TEDC – even with a sulfuric acid concentration of 8–13 g/dm3, TEDC reached the level of 1.35 g-eq/dm3, which corresponds to the sorption level of neutral dilute solutions. However, it can be seen from the total concentration that the efficiency of sorption of metals from acidic solutions remains quite high and increases with the increase of the initial total content of sorbed ions. The main indicator used when choosing an ion exchange method is the possibility of effective regeneration of the cation exchange material. When using a 5% solution of sulfuric acid already at the specific consumption of the regeneration solution, it was possible to achieve a degree of regeneration at the level of 95–98%, and when using a 10% solution, the degree of regeneration reached 100%. According to the research results, a technological scheme for processing regeneration solutions by precipitation of metals from regeneration solutions into magnetites in a ferritizer reactor was proposed.